Blue Zones-Based Worksite Nutrition Intervention: Positive Impact on Employee Wellbeing - Heath, Ciara; Lopez, Nanette V.; Seeton, Valerie; Sutliffe, Jay T. (Frontiers in Nutrition, 2022)
“Blue Zones” are geographical regions where people live to be nonagenarians and centenarians with significantly better rates of mental wellness when compared to the average American. It was discovered that these areas have nine unique evidenced-based lifestyle principles, with one of their main principles being the consumption of a plant-based diet. With this in mind, we performed a worksite intervention with the objective of understanding the relationships among Blue Zones knowledge, a plant-based lifestyle, and improvements in overall mental wellness during the COVID-19 pandemic. During spring 2021, we recruited 52 employees from a public, mid-sized university in the southwestern United States to participate in an 8-week virtual intervention that included weekly topic presentations, cooking demonstrations, and Blue Zones education. Participants were also assigned to weekly wellness counseling groups integrating Motivational Interviewing based principles that included additional, relevant conversation topics and support. The final sample (n=52 participants) had a mean age of 45.6±10.6 years. Participants were predominantly women (84.6%) and nearly half were married (44.2%). The majority attended graduate school (59.6%) and identified as White (84.6%). Paired-samples t-tests indicated significant improvements in all mental wellness outcomes and Healthy Eating Index-2015 (HEI-2015) scores over time (p’s <.001 to .02). Multiple linear regression models revealed that Blue Zones knowledge (β=-0.037, p=.010) significantly negatively predicted Patient Health Questionnaire-9 (PHQ-9) scores at 8-weeks. Additionally, multiple linear regression models indicated small group attendance (β=-1.51, p=.003) and Blue Zones knowledge (β=-0.81, p=.012) significantly negatively predicted sleep scores at 8-weeks. When HEI-2015 total scores were also included at baseline and 8-weeks (post-intervention), Blue Zones knowledge (β=-0.031, p=.049) was a borderline significant predictor of PHQ-9 at 8-weeks. Additionally, small group sessions (β=-1.52 p=.005) were a significant predictor of sleep at 8-weeks. The intervention illustrated that virtual intervention strategies can improve nutrition and mental wellness for future advancement in life quality and well-being.